Communication constrained robust guidance strategy using quantized artificial time delay based control with input saturation. Issue 18 (14th September 2021) - Banerjee, Arunava; Amrr, Syed Muhammad; Sarkar, Rajasree; Saidi, Abdelaziz Salah; Nabi, M.
Abstract: This work proposes the use of a logarithmic quantizer to minimize the computational load on the onboard processor of missiles. The quantizer output discretizes the continuous guidance command to a finite set of predefined discrete levels. This in turn puts an end to the need for installing a powerful state of the art modern processor onboard a missile, while enabling designers to install a comparatively cost efficient and compact processor. To include robustness properties, the proposed guidance strategy adopts the artificial time‐delayed control (TDC) philosophy. The use of TDC methodology eliminates the conservative assumptions of a priori knowledge about uncertainty bounds as required by most state‐of‐the‐art robust control schemes. Thus, the proposed guidance law is able to achieve interception even in the presence of uncertainties while significantly reducing control updates due to the use of input quantizer. Input saturation is also considered for the proposed quantized time‐delay control (QTDC) based guidance strategy. The Uniformly Ultimately Bounded (UUB) convergence of the closed‐loop system states is demonstrated through the Lyapunov theory. Simulation studies involving various engagement scenarios and a comparative performance study of the QTDC guidance scheme with the conventional periodic time‐triggered TDC technique are provided to highlight the efficacy of the proposed approach. In this work, a quantized input time delay based control is used to significantly reduce the control updates while designing an efficient robust control strategy. A sense of time‐energy efficiency is introduced for the overall system and input saturation is also considered.